War is not a game : the new antiwar soldiers and the movement they built - Levinson, Nan, 1949- (War culture., 2014)
On July 23, 2004, five marines, two soldiers, and one airman became the most unlikely of antiwar activists. Young and gung-ho when they first signed up to defend their country, they were sent to fight a war that left them confused, enraged, and haunted.